Złota elipsa i złota hiperbola - Janaszak, Tadeusz (Golden ellipse and golden hyperbola, 2011)
An ellipse, parabola and hyperbola are the curve that can be obtained as the plane section of cone; there are characterizations, one of which is by means of the focus and directrix property. The golden ellipse or the golden hyperbola is the curve, which has golden eccentricity
Didactics of Mathematics, 2011, Nr 8 (12), s. 55-69
Keywords: ellipse; hyperbola; parabola; focus; directrix; eccentricity; major axis; minor axis; equation of the ellipse; equations of the hyperbola; equation of the parabola; conic section curve